Identidad y reconocimiento, Charles Taylor en diálogo con el suma qamaña (buen vivir) aymara - Loza Márquez, Luis Ramiro (2021)
Who am I? is a question that seems to have lost relevance in these modern times. However, Charles Taylor, in his reflections on the concept of "identity", recovers this question, because the answer implies a "recognition" that is based on a dialogue with the different cultures, with one's own and with oneself. From such a perspective, this research will, on the one side, approach the concepts of "identity" and "recognition" developed by Taylor. On the other side, the Aymara cosmovision of Suma Qamaña (good living/living well) will be exposed.